Production of bioethanol from jackfruit rind-waste using Saccharomyces cerevisiae with crude enzyme treatment of Trichoderma reesei and Aspergillus niger - Teguh Cipta Rini; Trianik Widyaningrum (Journal on Biology and Instruction, 2021)
Production of bioethanol from jackfruit peel waste using Saccharomyces cerevisiae with crude enzyme ratio treatment of Trichoderma reesei and Aspergillus niger. Bioethanol is an alternative energy that is starting to be needed, along with the depletion of petroleum reserves. Bioethanol can be obtained from various wastes, one of which is jackfruit skin with the help of enzymes from T. reesei and A. niger and fermentation using S. cerevisiae. The purpose of this study was to determine the sugar content and the highest ethanol content of jackfruit peel waste using S. cerevisiae with the ratio treatment of crude enzymes T. reesei and A. niger. This research is experimental research. The experimental design used RAL with the independent variables being the ratio of crude enzymes T. reesei and A. niger, namely (1:0), (0:1), (1:1), (1:2), (2:1), (1:3), (3:1) and the dependent variable was the sugar and ethanol content of fermented jackfruit peel using S. cerevisiae. The measurement of sugar content using the DNS method, while the measurement of ethanol content using an alcoholmeter. Data analysis used one-way ANOVA (SPSS version 16). Based on the results of the study, the highest sugar content was in the ratio of crude enzymes T. reesei and A. niger after crude treatment 1:3 (14.21%) and after fermentation 1:2 (14.73%). The highest ethanol content was in the ratio of crude enzymes T. reesei and A. niger 1:1 (1,32%).